Load-bearing type high-temperature bedplate and manufacturing method thereof

By using the staggered structure outer layer of low zirconium corundum and plate-shaped corundum in high-temperature plates, as well as the inner layer staggered structure of white corundum and other materials, the problems of insufficient compressive strength and thermal shock resistance stability of existing high-temperature plates are solved. , achieving higher compressive strength, wear resistance and longer service life.

CN119462103AActive Publication Date: 2025-02-18JIANGSU SANHENG HIGH-TECH KILN FURNITURE CO LTD

Patent Information

Application Number
CN202411663090.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

When existing high-temperature plates withstand pressure and thermal shock in high-temperature environments, their pressure resistance and thermal shock resistance are insufficient, resulting in short service life and prone to breaking and deformation.

Method used

Low zirconium corundum and plate-shaped corundum are used as outer material. The zircon fine powder is sprayed in an atomization to form an interlaced structure. The inner material is made of white corundum, electromelite, rosystone and zircon, and plate-shaped corundum fine powder. Through atomization spraying, an interlaced structure in which zirconium corundum crystals are filled in the mullite network gap is formed through high-pressure molding and sintering processes.

Benefits of technology

It significantly improves the pressure strength, wear resistance and thermal shock resistance of the table plate, extends the service life, and improves the reliability of performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143945570000031
    Figure BDA0005143945570000031
  • Figure BDA0005143945570000041
    Figure BDA0005143945570000041
  • Figure BDA0005143945570000071
    Figure BDA0005143945570000071
Patent Text Reader

Abstract

The invention belongs to the field of advanced structure ceramic preparation, and particularly relates to a load-bearing type high-temperature bedplate and a manufacturing method thereof. The preparation method of the load-bearing type high-temperature bedplate comprises the following steps: (1) sequentially paving the outer layer material, the inner layer material and the outer layer material into a mold, and carrying out high-pressure forming to obtain a formed blank; (2) drying the formed blank to obtain a dry blank; and (3) firing the dry blank at the temperature of 1550-1680 DEG C to obtain the bedplate. The preparation method comprises the following steps: by taking low-zirconium corundum, white corundum, fused mullite and andalusite as raw materials, introducing zirconite and tabular corundum fine powder, and respectively preparing an outer layer material and an inner layer material; the high-strength wear-resistant bedplate with a low-zirconia corundum outer layer and a staggered structure in which zirconia corundum crystals are filled in gaps of a mullite network is formed through pressure forming and sintering, has good high-temperature strength and excellent thermal shock resistance, can bear constantly changing impact of high-low temperature circulation of a pushed slab kiln, and has long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced structural ceramic preparation, in particular to a heavy-load-type high-temperature table plate and a manufacturing method thereof. Background Art

[0002] The platen, also known as the push plate, is a key component in the push plate kiln that carries the product forward. It must not only meet the high-temperature atmosphere conditions for sintering, but also require the platen (generally only 30mm thick) to withstand a pressure of 20-30kg / plate, as well as the long-distance (about 30M) pushing and squeezing force of the burned product, and withstand the impact of high and low temperature changes caused by the long-term cycle from room temperature → high temperature → room temperature (cycle in the furnace once every 20-30 hours or so). At the same time, it is required to have a long service life. During use, even if a small piece of the push plate is broken, falls off, climbs on the plate, sticks or deforms, it will cause the entire push plate to be unable to continue to advance, and the kiln will be forced to stop for a major accident of turning over the top, causing great economic losses to the user. Therefore, the platen is required to have excellent high temperature strength and wear resistance, good thermal shock stability and volume stability, and extremely high comprehensive performance requirements.

[0003] At present, mullite platens are usually used in the market. Platens made of other materials, such as cordierite and corundum, are not suitable because of their low refractoriness and large expansion. Silicon carbide platens are not suitable because they are not resistant to oxidation in an oxidizing atmosphere. For example, Chinese patent CN1763465 discloses a push plate for a soft ferrite sintering nitrogen kiln, the weight percentage of which is: fused mullite 0.5-3mm 40-45%, 0.06-0.5mm 5-8%, <0.04mm18-22%, plate-shaped corundum 0.5-3mm 8-12%, fused white corundum 0.06-0.5mm 1-3%, α-alumina <0.045mm 10-14%, <4um 4-6%, silicon dioxide powder 2-4%, and silicon aluminum gel 8-9%. This push plate for a soft ferrite sintering nitrogen kiln can only be used in a nitrogen kiln below 1450°C.

[0004] Chinese patent CN201410809937.3 discloses a high-performance modified mullite high-temperature platen and preparation process, the weight percentage is: fused mullite ≤3mm 40-50%, plate-shaped corundum ≤3mm 20-35%, α-alumina ≤320 mesh 12-20%, spinel ≤200 mesh 3-5%, kaolin ≤200 mesh 7-10%, lanthanum oxide yttrium oxide composite rare earth additive ≤1um 0.5-1%, the mass ratio of yttrium oxide to lanthanum oxide in the lanthanum oxide yttrium oxide composite rare earth additive is 1:0.05-0.3. The patent has good thermal shock resistance and high temperature strength, but after long-term use, due to insufficient high temperature bearing capacity and insufficient strength, the pushing surface and loading surface of the push plate are prone to large changes due to force extrusion, increase in size, bending deformation, and even fracture, which reduces the service life. Summary of the invention

[0005] The present invention provides a heavy-load high-temperature table plate, which is suitable for a push-plate kiln with a temperature of 1650°C or below. The table plate can withstand a pressure of 40-60kg / plate when in use, and the load capacity is greatly improved. It also has a stable volume, a long service life, and reliable performance. Therefore, the table plate of the present invention has higher compressive strength, stronger wear resistance, and better thermal shock resistance stability.

[0006] The object of the present invention is to provide a heavy-duty high-temperature table.

[0007] The object of the present invention is to provide a method for preparing the above-mentioned heavy-load-type high-temperature platen.

[0008] According to a specific embodiment of the present invention, a method for preparing a heavy-duty high-temperature platen comprises the following steps:

[0009] (1) The outer layer material, the inner layer material, and the outer layer material are laid flatly into the mold from bottom to top in a mass ratio of 1-2:6-8:1-2, and high-pressure molding is performed at a pressure of 200-250 MPa to obtain a molded blank; wherein,

[0010] (2) drying the formed blank until the moisture content is less than 1% to obtain a dry blank;

[0011] (3) Sintering the dry blank at a temperature of 1550-1680° C. to obtain the table plate.

[0012] According to the method for preparing a heavy-loaded high-temperature tabletop in a specific embodiment of the present invention, the raw materials of the outer layer material include, by weight: 4 to 5 parts of low-zirconium corundum, 4 to 5.5 parts of plate-shaped corundum and 0.8 to 1.5 parts of zircon, wherein the surface of the low-zirconium corundum and the surface of the plate-shaped corundum are coated with zircon.

[0013] According to the method for preparing a heavy-duty high-temperature platen in a specific embodiment of the present invention, the particle size of the low-zirconium corundum is 3 to 1 mm; and / or,

[0014] The particle size of the plate-like corundum is 1 to 0.125 mm; and / or,

[0015] The particle size of zircon is ≤50um.

[0016] According to the method for preparing a heavy-duty high-temperature platen in a specific embodiment of the present invention, the steps of coating the surface of low-zirconium corundum and the surface of plate-shaped corundum with zircon are as follows:

[0017] Mix 4-5 parts of low-zirconium corundum and 4-5.5 parts of plate-shaped corundum to obtain a mixed dry material;

[0018] Zircon is prepared into a mixed solution with a concentration of 70-85%;

[0019] The mixed liquid is atomized and sprayed into the mixed dry material to obtain the outer layer material.

[0020] Preferably, zircon is prepared into a mixed solution with a concentration of 70-85% by using a PVA solution, and the concentration of the PVA solution is 1-1.5%.

[0021] According to the method for preparing a heavy-loaded high-temperature tabletop in a specific embodiment of the present invention, the raw materials of the inner layer material include, by weight: 3 to 4 parts of white corundum, 0.8 to 1.5 parts of fused mullite, 0.8 to 1.5 parts of andalusite, 0.8 to 1.5 parts of zircon and 1.3 to 2.5 parts of plate-like corundum, wherein the surfaces of the white corundum, fused mullite, andalusite and zircon are coated with plate-like corundum.

[0022] According to the method for preparing a heavy-duty high-temperature platen according to a specific embodiment of the present invention, the particle size of the white corundum is 2 mm to 0.5 mm; and / or,

[0023] The particle size of the fused mullite is 0.5 to 0.125 mm; and / or,

[0024] The particle size of andalusite is 2 mm to 0.5 mm; and / or,

[0025] The particle size of zircon is 3 mm to 0.5 mm; and / or,

[0026] The particle size of plate-shaped corundum is ≤50um.

[0027] According to the method for preparing a heavy-duty high-temperature platen in a specific embodiment of the present invention, the inner layer material is prepared by the following steps:

[0028] Mix 3-4 parts of white corundum, 0.8-1.5 parts of fused mullite, 0.8-1.5 parts of andalusite, and 0.8-1.5 parts of zircon to obtain a mixed dry material;

[0029] Prepare a mixed solution of plate-shaped corundum with a concentration of 45-60%;

[0030] The mixed liquid is atomized and sprayed into the mixed dry material to obtain the inner layer material.

[0031] Preferably, the plate-shaped corundum is prepared into a mixed solution with a concentration of 45-60% by using a PVA solution, and the concentration of the PVA solution is 1-1.5%.

[0032] According to the method for preparing a heavy-duty high-temperature platen in a specific embodiment of the present invention, in step (3), the dry blank is fired according to the following temperature program:

[0033]

[0034]

[0035] The present invention provides a heavy-duty high-temperature table plate prepared by the above method, which can control the decomposition ratio of large-particle zircon and andalusite raw materials and the distribution of the interlaced structure of the crystal phases inside the table plate, form an interlaced structure in which zirconium corundum crystals are filled in the gaps of the mullite network, and obtain a high-strength wear-resistant table plate with a low-zirconium corundum outer layer.

[0036] Beneficial effects of the present invention:

[0037] The present invention uses different formulas for the inner and outer layers of the tabletop. The outer layer uses low-zirconium corundum and plate-shaped corundum particles as raw materials, and zircon powder is added thereto in an atomized form; the inner layer uses white corundum, fused mullite, andalusite, and zircon particles as raw materials, and plate-shaped corundum powder is introduced thereto in an atomized form. The outer layer material, the inner layer material, and the outer layer material are added and scraped in proportion, and the materials are evenly distributed, and then pressure is applied to form the blank. After the blank is dried, it is sintered to form an interlaced structure in which zirconium corundum crystals fill the gaps in the mullite network. The inner and outer layers react with the materials to form an integrated crystal interlaced network, which not only strengthens the wear resistance of the outer layer of the tabletop, but also enhances the structural strength of the inner layer, that is, the high-strength wear-resistant tabletop with a low-zirconium corundum outer layer of the present invention.

[0038] The micro powder atomization process is introduced when the raw materials are mixed to form droplets of 50 to 100 um. After sufficient mixing, the surface of the granular material evenly adsorbs the micro powder, with less agglomeration and good uniformity of particle grading distribution, which is convenient for the molding and pressing process and ensures the uniformity and reliability of the internal micro structure of the platen. DETAILED DESCRIPTION

[0039] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0040] The method for preparing the heavy-duty high-temperature platen of the present invention comprises the following steps:

[0041] (1) The outer layer material, the inner layer material, and the outer layer material are laid flatly into the mold from bottom to top in a mass ratio of 1-2:6-8:1-2, and high-pressure molding is performed at a pressure of 200-250 MPa to obtain a molded blank;

[0042] (2) drying the formed blank until the moisture content is less than 1% to obtain a dry blank;

[0043] (3) Sintering the dry blank at a temperature of 1550-1680° C. to obtain the table plate.

[0044] Wherein, the preparation method of the outer layer material is:

[0045] Put 4.0-5.0 parts by weight of low-zirconium corundum with a particle size of 3-1 mm and 4.0-5.5 parts by weight of plate-shaped corundum with a particle size of 1-0.125 mm into a mixer and dry mix for 0.5-1 hour.

[0046] Add 1-1.5% PVA to 0.8-1.5 parts by mass of zircon with a particle size of ≤50um to prepare a mixed liquid with a concentration of 70-85%, stir it with a homogenizer pump for 20-30 minutes until it is evenly stirred, and then transport it to an atomizing nozzle through a medium and low pressure diaphragm pump, spray it into the mixed dry material, and then mix it for 0.5-1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 3-8%, and the mixture is set aside for use.

[0047] Preferably, the content of low-zirconium corundum is 4.2 to 4.6 parts by weight; the content of plate-shaped corundum is 4.4 to 5.2 parts by weight; and the content of zircon is 1.0 to 1.3 parts by weight.

[0048] The outer layer material is low-zirconium corundum and plate-shaped corundum raw materials, and zircon is introduced in the form of micro-powder atomization. Compared with corundum or corundum mullite, low-zirconium corundum has better wear resistance, thermal shock resistance and high compressive strength, and can withstand high temperature and high pressure, and thermal shock of rapid changes in temperature. Plate-shaped corundum has strong chemical inertness and is produced by high-temperature calcination and rapid cooling. There are tiny bumps on the surface of the crystal particles, and there are evenly distributed micropores inside the particle structure, which has strong activity. Zircon has high chemical stability and extremely strong corrosion resistance, small thermal expansion coefficient, good toughness. After high-temperature sintering, most of the fine powder is decomposed into t-ZrO2 and SiO2, and a small amount of mullite phase main crystal phase and SiO2 liquid phase appear. Zircon reacts with plate-like corundum at high temperature to form a staggered grid structure with a modified zirconium-corundum-mullite complex phase, which has good compressive strength and excellent thermal shock resistance. Zircon and low-zirconium corundum particles react and combine, and the product has better high-temperature wear resistance. Therefore, compared with the table top of the corundum-mullite phase, the load performance of the table top of the present invention is greatly improved and enhanced.

[0049] Preferably, the concentration of zircon in the mixed solution is 75-82%.

[0050] Preferably, the moisture content of the mixture is 3-6%.

[0051] The preparation method of the inner layer material is:

[0052] 3.0-4.0 parts by weight of white corundum with a particle size of 2 mm to 0.5 mm, 1.5-2.5 parts by weight of fused mullite with a particle size of 0.5 mm to 0.125 mm, 0.8-1.5 parts by weight of andalusite with a particle size of 2 mm to 0.5 mm, and 0.8-1.5 parts by weight of zircon with a particle size of 3 mm to 0.5 mm, are dry mixed for 0.5-1 hour;

[0053] Add 1-1.5% PVA to 1.3-2.5 parts by mass of plate-shaped corundum with a particle size of ≤50um to prepare a mixed liquid with a concentration of 45-60%, stir it with a homogenizer pump for 20-30 minutes until it is evenly stirred, and then transport it to an atomizing nozzle through a medium and low pressure diaphragm pump, spray it into the mixed dry material, and then mix it for 0.5-1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 3-8%, and the mixture is set aside for use.

[0054] Preferably, white corundum is 3.3-3.8 parts; fused mullite is 1.7-2.3 parts; andalusite is 1.0-1.3 parts; zircon is 1.0-1.3 parts; and plate-shaped corundum is 1.6-2.2 parts.

[0055] The inner layer material is made of white corundum, fused mullite, andalusite, and zircon particles, and the plate-shaped corundum is introduced in the form of micro-powder atomization.

[0056] Among them, white corundum has stable chemical properties, high purity, good high temperature thermal stability, and is a high-quality refractory aggregate. Fused mullite has stable chemical properties, small linear expansion, and good thermal shock resistance. Andalusite fine powder can be completely transformed into an irreversible mullite phase main crystal phase and dissociate free SiO2 at high temperature. Free SiO2 can react with the introduced plate-like corundum phase to produce a secondary mullite reaction, which increases the content of mullite phase inside the product, reduces the free SiO2 entering the liquid phase, improves the crystal phase microstructure, and improves the high temperature performance and thermal shock resistance of the product. Zircon has good chemical inertness. Fine powder begins to decompose into t-ZrO2 and SiO2 at a temperature of 1540℃, and a small amount of mullite phase main crystal phase and SiO2 liquid phase appear.

[0057] Through high-temperature sintering, the inner layer material forms a skeleton network with corundum and zirconium oxide grains embedded in the needle-shaped modified mullite crystal phase, forming an interlaced structure of zirconium corundum crystals filled in the mullite network, which enhances the high-temperature strength and thermal shock resistance of the product and greatly improves the load capacity.

[0058] The present invention optimizes the particle ratio of the raw materials of the inner layer, and controls the particle composition and the firing temperature curve so that a small portion of large particles of andalusite and a portion of large particles of zircon are not completely decomposed, so that they can slowly decompose and react in the later use process, and are further converted into mullite, monoclinic zirconium and glass phase SiO2. A part of the glass phase SiO2 promotes the combination of corundum and mullite, and improves the strength of the composite phase interlaced network structure, and the other part is secondary mullitized with the plate-like corundum micropowder, thereby improving the fracture energy of the table plate, playing a modification and toughening role, and promoting the table plate to have a longer service life.

[0059] Preferably, the concentration of the plate-like corundum in the mixed solution is 50-58%.

[0060] Preferably, the moisture content of the mixture is 3-6%.

[0061] In step (1), the inner and outer layer mixed materials that have been trapped for 36 to 48 hours are weighed and distributed according to the mass proportion of the product, and are distributed into the mold cavity in sequence. After the materials are scraped and leveled, a pressure of 200-250 MPa is applied by a molding hydraulic press for high-pressure molding. The pressure is applied slowly, and the pressure is maintained for multiple times to exclude the air in the blank, so as to obtain a compact blank without interlayer.

[0062] In step (2), the blank is naturally stored for 24 to 36 hours, and after the internal stress is released, it is placed in a drying room for drying. After drying in two temperature ranges of 60 to 100° C. and 100 to 150° C., a dry blank with a moisture content of less than 1% is obtained, which is ready for loading into the kiln.

[0063] In step (3), the high temperature roasting system is as follows:

[0064]

[0065]

[0066] The qualified blanks are loaded into the kiln and fired at a maximum firing temperature of 1680°C by optimizing the firing curve, so as to control the decomposition and synthesis ratio of large-particle zircon and andalusite raw materials and the distribution of the interlaced crystal structure inside the table plate, forming an interlaced structure in which zirconium-corundum crystals fill the gaps in the mullite network, and a high-strength wear-resistant table plate with a low-zirconium-corundum outer layer.

[0067] Example 1

[0068] The method for preparing the heavy-duty high-temperature platen of the present invention comprises the following steps:

[0069] 1. Raw material preparation:

[0070] (1) Outer layer material: 45 parts by weight of low-zirconium corundum with a particle size of 3 to 1 mm and 46 parts by weight of plate-shaped corundum with a particle size of 1 to 0.125 mm are placed in a mixer and dry-mixed for 1 hour to obtain a mixed dry material.

[0071] 9 parts by mass of zircon with a particle size of ≤50 um was added with 1.5% PVA to prepare a mixed liquid with a concentration of 76%, and the mixture was stirred with a homogenizing pump for 20 to 30 minutes until it was evenly stirred to obtain a mixed liquid.

[0072] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 0.5 to 1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 3.5%, and the mixture is set aside for use;

[0073] (2) Inner layer material: 38 parts by weight of white corundum with a particle size of 2 mm to 0.5 mm, 22 parts by weight of fused mullite with a particle size of 0.5 mm to 0.125 mm, 11 parts by weight of andalusite with a particle size of 2 mm to 0.5 mm, and 12 parts by weight of zircon with a particle size of 3 mm to 0.5 mm, are dry-mixed for 0.5 to 1 hour to obtain a mixed dry material.

[0074] 17 parts by mass of plate-shaped corundum with a particle size of ≤50 um was added with 1% PVA to prepare a mixed liquid with a concentration of 52%, and the mixture was stirred with a homogenizing pump for 20 to 30 minutes until it was evenly stirred to obtain a mixed liquid.

[0075] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 0.5 hours to obtain a uniform mixture. The moisture content of the mixture is controlled at 3%, and the mixture is stored for use;

[0076] 2. Pressing and drying of molding:

[0077] The inner and outer layer mixed materials that have been trapped for 36 to 48 hours, the outer layer material, the inner layer material, and the outer layer material are weighed and laid in a mass ratio of 1:6:1, and are placed in the mold cavity in the order of outer layer material, inner layer material, and outer layer material. After the materials are scraped and leveled, a molding hydraulic press is used to apply a pressure of 200-250MPa for high-pressure molding. The pressure is applied slowly and the pressure is maintained for multiple times to exclude the air in the blank to obtain a densely molded blank without interlayer.

[0078] The blanks are naturally stored for 30 hours, and after the internal stress is released, they are placed in a drying room for drying. After drying in two temperature zones of 80°C and 120°C, dry blanks with a moisture content of less than 1% are obtained, which are ready to be loaded into the kiln.

[0079] 3. High temperature roasting:

[0080] The qualified blanks are loaded into the kiln and fired according to the high temperature roasting preparation:

[0081]

[0082] Example 2

[0083] The method for preparing the heavy-duty high-temperature platen of the present invention comprises the following steps:

[0084] 1. Raw material preparation:

[0085] (1) Outer layer material: 40 parts by weight of low-zirconium corundum with a particle size of 3 to 1 mm and 40 parts by weight of plate-shaped corundum with a particle size of 1 to 0.125 mm are placed in a mixer and dry-mixed for 0.5 hours to obtain a mixed dry material.

[0086] 8 parts by mass of zircon with a particle size of ≤50 um was added with 1% PVA to prepare a mixed liquid with a concentration of 70%, and the mixture was stirred for 20 minutes by a homogenizing pump until it was evenly stirred to obtain a mixed liquid.

[0087] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 3%, and the mixture is set aside for use;

[0088] (2) Inner layer material: 30 parts by weight of white corundum with a particle size of 2 mm to 0.5 mm, 15 parts by weight of fused mullite with a particle size of 0.5 mm to 0.125 mm, 8 parts by weight of andalusite with a particle size of 2 mm to 0.5 mm, and 8 parts by weight of zircon with a particle size of 3 mm to 0.5 mm were dry-mixed for 0.5 hour to obtain a mixed dry material.

[0089] 13 parts by mass of plate-shaped corundum with a particle size of ≤50 um was added with 1% PVA to prepare a mixed liquid with a concentration of 45%, and the mixture was stirred with a homogenizing pump for 20 to 30 minutes until it was evenly stirred to obtain a mixed liquid.

[0090] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 0.5 hours to obtain a uniform mixture. The moisture content of the mixture is controlled at 3%, and the mixture is stored for use;

[0091] 2. Pressing and drying of molding:

[0092] The inner and outer layer mixed materials that have been trapped for 36 hours, the outer layer material, the inner layer material, and the outer layer material are weighed and laid according to the mass ratio of 1.5:7:1.5, and are placed into the mold cavity in the order of outer layer material, inner layer material, and outer layer material. After the materials are scraped and leveled, a molding hydraulic press is used to apply a pressure of 200-250MPa for high-pressure molding. The pressure is applied slowly and the pressure is maintained for multiple times to exclude the air in the blank to obtain a densely molded blank without interlayer.

[0093] The blanks are naturally stored for 24 hours, and after the internal stress is released, they are placed in a drying room for drying. After drying at two temperature zones of 60°C and 100°C, dry blanks with a moisture content of less than 1% are obtained, which are ready to be loaded into the kiln.

[0094] 3. High temperature roasting:

[0095] The qualified blanks are loaded into the kiln and fired according to the high temperature roasting preparation:

[0096]

[0097]

[0098] Example 3

[0099] The method for preparing the heavy-duty high-temperature platen of the present invention comprises the following steps:

[0100] 1. Raw material preparation:

[0101] (1) Outer layer material: 50 parts by weight of low-zirconium corundum with a particle size of 3 to 1 mm and 55 parts by weight of plate-shaped corundum with a particle size of 1 to 0.125 mm are placed in a mixer and dry mixed for 1 hour to obtain a mixed dry material.

[0102] 15 parts by mass of zircon with a particle size of ≤50 um was added with 1.5% PVA to prepare a mixed liquid with a concentration of 85%, and the mixture was stirred with a homogenizing pump for 30 minutes until it was evenly stirred to obtain a mixed liquid.

[0103] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 5%, and the mixture is stored for use;

[0104] (2) Inner layer material: 40 parts by weight of white corundum with a particle size of 2 mm to 0.5 mm, 25 parts by weight of fused mullite with a particle size of 0.5 mm to 0.125 mm, 15 parts by weight of andalusite with a particle size of 2 mm to 0.5 mm, and 15 parts by weight of zircon with a particle size of 3 mm to 0.5 mm were dry-mixed for 1 hour to obtain a mixed dry material.

[0105] 25 parts by mass of plate-shaped corundum with a particle size of ≤50 um was added with 1.5% PVA to prepare a mixed liquid with a concentration of 60%, and the mixture was stirred with a homogenizing pump for 30 minutes until it was evenly stirred to obtain a mixed liquid.

[0106] The mixed liquid is transported to the atomizing nozzle by a medium-low pressure diaphragm pump, sprayed into the mixed dry material, and then mixed for 1 hour to obtain a uniform mixture. The moisture content of the mixture is controlled at 6%, and the mixture is set aside for use;

[0107] 2. Pressing and drying of molding:

[0108] The inner and outer layer mixed materials that have been trapped for 48 hours, the outer layer material, the inner layer material, and the outer layer material are weighed and laid in a mass ratio of 2:8:2, and are placed in the mold cavity in the order of outer layer material, inner layer material, and outer layer material. After the materials are scraped and leveled, a hydraulic press is used to apply a pressure of 200-250MPa for high-pressure molding. The pressure is applied slowly and the pressure is maintained for multiple times to exclude the air in the blank to obtain a densely molded blank without interlayer.

[0109] The blanks are naturally stored for 36 hours, and after the internal stress is released, they are placed in a drying room for drying. After drying in two temperature zones of 100°C and 150°C, dry blanks with a moisture content of less than 1% are obtained, which are ready to be loaded into the kiln.

[0110] 3. High temperature roasting:

[0111] The qualified blanks are loaded into the kiln and fired according to the high temperature roasting preparation:

[0112]

[0113]

[0114] Comparative Example 1

[0115] The difference from Example 1 is that the zircon in the outer layer material is directly added to the low-zirconium corundum and plate-shaped corundum in the form of powder for mixing, and the other steps are the same as Example 1.

[0116] Comparative Example 2

[0117] The difference from Example 1 is that the plate-shaped corundum in the inner layer material is directly added to the white corundum, fused mullite, andalusite and zircon in powder form for mixing, and the other steps are the same as Example 1.

[0118] Comparative Example 3

[0119] The difference from Example 1 lies in the firing system. When the firing temperature reaches 1680°C, the holding time is only 0.5 hours. The other steps are the same as Example 1.

[0120] Comparative Example 4

[0121] The difference from Example 1 lies in the firing system. When the firing temperature reaches 1650°C, it is kept warm for 1-2 hours and then cooled. The other steps are the same as Example 1.

[0122] Comparative Example 5

[0123] The difference from Example 1 is that the andalusite and zircon in the inner layer material are replaced with fine powder, wherein the andalusite particles are 0.05-0.125 mm, and the zircon particles are 0.05-0.125 mm. The other steps are the same as Example 1.

[0124] The compressive strength and thermal shock resistance of the tabletops obtained in Examples 1-3 and Comparative Examples 1-5 were tested respectively.

[0125] The compressive strength test method of the tabletop: GB / T5072-2008 Test method for compressive strength of refractory materials at room temperature. The thermal shock resistance test method of the tabletop: YB / T376.1-1995 Test method for thermal shock resistance of refractory products (water quenching method).

[0126] The experimental results are as follows:

[0127] Table 1 Performance test data of the table

[0128] Compressive strength(MPa) Thermal shock times (times) Example 1 132 63 Example 2 135 65 Example 3 124 55 Comparative Example 1 106 35 Comparative Example 2 116 37 Comparative Example 3 110 48 Comparative Example 4 115 26 Comparative Example 5 112 42

[0129] As can be seen from Table 1, the tabletop of Example 3 has a large mass fraction of andalusite and zircon, and forms a large amount of SiO2 liquid phase after high-temperature sintering and dissociation, which leads to a decrease in the high-temperature load softening of the formed material, thereby reducing the high-temperature strength of the material. The compressive strength and thermal shock resistance of the obtained tabletop are lower than those of the tabletops of Examples 1 and 2. At the same time, the compressive strength and thermal shock resistance of the tabletops described in Examples 1-3 are significantly better than those of Comparative Examples 1-5.

[0130] In comparative example 1, zircon in the outer layer material is directly added into low-zirconium corundum and plate-like corundum in powder form for mixing. Since the zircon powder cannot be evenly wrapped on the surface of other granular materials, the zirconium-containing corundum mullite locally generated after high-temperature sintering of zircon dissociates and forms mullite with the plate-like corundum leads to an incomplete crystal network structure, thereby affecting the high-temperature strength and wear resistance of the material. The compressive strength and thermal shock resistance of the obtained table plate are greatly reduced.

[0131] In comparative example 2, the plate-like corundum in the inner layer material is directly added to the white corundum, fused mullite, andalusite and zircon in powder form and mixed. Since the plate-like corundum powder cannot be evenly wrapped on the surface of other granular materials, the high-temperature sintered zircon and andalusite do not react completely with the plate-like corundum after dissociation, and there is an excess of SiO2 liquid phase locally, resulting in the local formation of a zirconium-containing corundum mullite network structure, thereby reducing the high-temperature softening and strength of the material, and the compressive strength and thermal shock resistance of the resulting table plate are greatly reduced.

[0132] Comparative Example 3 differs from Example 1 in the firing system. When the firing temperature reaches 1680°C, the holding time is only 0.5 hours. The SiO2 phase generated after dissociation in the andalusite and zircon particles in the inner layer material is relatively small, and the zirconium-containing corundum mullite phase generated by the reaction with the plate-like corundum is insufficient, resulting in only partial formation of the zirconium-containing corundum mullite network structure, thereby reducing the high-temperature softening and strength of the material, and the compressive strength and thermal shock resistance of the resulting tabletop are greatly reduced.

[0133] Comparative Example 4 differs from Example 1 in the firing system. When the firing temperature reaches 1650°C, the holding time is only 1-2 hours, the zircon particles in the inner layer material are insufficiently dissociated, and the generated SiO2 phase is even less. A small part reacts with the plate-like corundum to form a corundum mullite phase, resulting in only a small part of the formation of a mullite network structure, thereby greatly reducing the high-temperature softening and strength of the material, and the compressive strength and thermal shock resistance of the resulting tabletop are greatly reduced.

[0134] Comparative Example 5 is different from Example 1 in that the andalusite and zircon in the inner layer material are replaced with fine powder. The temperature required for the dissociation of the fine powder is low. After high-temperature sintering, the andalusite and zircon are completely dissociated to form an excess of SiO2 liquid phase, resulting in a decrease in the high-temperature softening of the formed material, thereby reducing the high-temperature strength of the material. The compressive strength and thermal shock resistance of the resulting table plate are reduced.

[0135] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a heavy-duty high-temperature platen, characterized in that: The preparation method comprises the following steps: (1) The outer layer material, the inner layer material, and the outer layer material are laid flatly into the mold from bottom to top in a mass ratio of 1-2:6-8:1-2, and high-pressure molding is performed at a pressure of 200-250 MPa to obtain a molded blank; (2) drying the formed blank until the moisture content is less than 1% to obtain a dry blank; (3) Sintering the dry blank at a temperature of 1550-1680° C. to obtain the table plate.

2. The method for preparing a heavy-duty high-temperature platen according to claim 1, characterized in that: In parts by weight, the raw materials of the outer layer material include: 4-5 parts of low-zirconium corundum, 4-5.5 parts of plate-shaped corundum and 0.8-1.5 parts of zircon, wherein the surface of the low-zirconium corundum and the surface of the plate-shaped corundum are coated with zircon.

3. The method for preparing a heavy-duty high-temperature platen according to claim 2, characterized in that: The particle size of low zirconium corundum is 3 to 1 mm; and / or, The particle size of the plate-like corundum is 1 to 0.125 mm; and / or, The particle size of zircon is ≤50um.

4. The method for preparing a heavy-duty high-temperature platen according to claim 2 or 3, characterized in that: The steps of coating the surface of low-zirconium corundum and plate-shaped corundum with zircon are as follows: Mix 4-5 parts of low-zirconium corundum and 4-5.5 parts of plate-shaped corundum to obtain a mixed dry material; Zircon is prepared into a mixed solution with a concentration of 70-85%; The mixed liquid is atomized and sprayed into the mixed dry material to obtain the outer layer material.

5. The method for preparing a heavy-duty high-temperature platen according to claim 1, characterized in that: In terms of weight, the raw materials of the inner layer material include: 3 to 4 parts of white corundum, 0.8 to 1.5 parts of fused mullite, 0.8 to 1.5 parts of andalusite, 0.8 to 1.5 parts of zircon and 1.3 to 2.5 parts of plate-like corundum, wherein the surfaces of white corundum, fused mullite, andalusite and zircon are coated with plate-like corundum.

6. The method for preparing a heavy-duty high-temperature platen according to claim 5, characterized in that: The particle size of white corundum is 2 mm to 0.5 mm; and / or, The particle size of the fused mullite is 0.5 to 0.125 mm; and / or, The particle size of andalusite is 2 mm to 0.5 mm; and / or, The particle size of zircon is 3 mm to 0.5 mm; and / or, The particle size of plate-shaped corundum is ≤50um.

7. The method for preparing a heavy-duty high-temperature platen according to claim 5, characterized in that: Mix 3-4 parts of white corundum, 0.8-1.5 parts of fused mullite, 0.8-1.5 parts of andalusite, and 0.8-1.5 parts of zircon to obtain a mixed dry material; Prepare a mixed solution of plate-shaped corundum with a concentration of 45-60%; The mixed liquid is atomized and sprayed into the mixed dry material to obtain the inner layer material.

8. The method for preparing a heavy-duty high-temperature platen according to claim 1, characterized in that: In step (3), the dry blank is fired according to the following temperature program:

9. The heavy-loaded high-temperature platen obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-performance modified mullite high-temperature bedplate as well as manufacturing method

    CN104591753A

  • Alumina low-cement spraying material

    CN103232251A

  • High-wear-proof high-thermal-shock-resistant fire-proof material and prefabricated furnace mouth part made from same

    CN103435361A

  • High-strength wear-resistant push plate for high-temperature push plate kiln

    CN108036641A

  • Bending-resistant high-temperature composite load bearing board and preparation method thereof

    CN111056825A

Cited By

  • High-purity corundum brick with high thermal shock resistance and preparation method thereof

    CN120483693A

  • High-thermal-shock-resistance high-purity corundum brick and preparation method thereof

    CN120483693B